A virtual system-coupled molecular dynamics simulation free from experimental knowledge on binding sites: Application to RNA-ligand binding free-energy landscape - Junichi Higo; Kota Kasahara; Shun Sakuraba; Gert-Jan Bekker; Narutoshi Kamiya; Ikuo Fukuda; Takuya Takahashi; Yoshifumi Fukunishi (Biophysics and Physicobiology)
Ligand–receptor docking simulation is difficult when the biomolecules have high intrinsic flexibility. If some knowledge on the ligand–receptor complex structure or inter-molecular contact sites are presented in advance, the difficulty of docking problem considerably decreases. This paper proposes a generalized-ensemble method “cartesian-space division mD-VcMD” (or CSD-mD-VcMD), which calculates stable complex structures without assist of experimental knowledge on the complex structure. This method is an extension of our previous method that requires the knowledge on the ligand–receptor complex structure in advance. Both the present and previous methods enhance the conformational sampling, and finally produce a binding free-energy landscape starting from a completely dissociated conformation, and provide a free-energy landscape. We applied the present method to same system studied by the previous method: A ligand (ribocil A or ribocil B) binding to an RNA (the aptamer domain of the FMN riboswitch). The two methods produced similar results, which explained experimental data. For instance, ribocil B bound to the aptamer’s deep binding pocket more strongly than ribocil A did. However, this does not mean that two methods have a similar performance. Note that the present method did not use the experimental knowledge of binding sites although the previous method was supported by the knowledge. The RNA-ligand binding site could be a cryptic site because RNA and ligand are highly flexible in general. The current study showed that CSD-mD-VcMD is actually useful to obtain a binding free-energy landscape of a flexible system, i.e., the RNA-ligand interacting system.